Synthesis of new Conjugates of some NSAIDs with Sulfonamide as Possible Mutual Prodrugs using Tyrosine Spacer for Colon Targeted Drug Delivery - L. Abdulhadi, Shayma; J. Qasir, Ahlam; A. Abdul Razzak, Nadeem (Iraqi Journal of Pharmaceutical Sciences, 2017)
The purpose of this research work is to synthesize conjugates of some NSAIDs with sulfamethoxazole as possible mutual prodrugs to overcome the local gastric irritation of NSAID with free carboxyl group by formation of ester linkage that supposed to remain intact in stomach and may hydrolyze in intestine chemically or enzymatically; in addition to that attempting to target the synthesized derivative to the colon by formation of azo group that undergo reduction only by colonic bacterial azo reductaze enzyme to liberate the parent compound to act locally (treatment of inflammation and infections in colon).Key words: Mutual prodrug, Ester linkage, Azo bond, Colon targeting